Detrimental correlation between air pollution with skin aging in Taiwan population. Issue 31 (5th August 2022) - Huang, Chao-Hsin; Chen, Szu-Chia; Wang, Yi-Chian; Wang, Chen-Feng; Hung, Chih-Hsing; Lee, Su-Shin
Abstract : Dissecting the complex relationships between skin aging and air pollution has been an ongoing effort. The increased exposure to air pollution over time imposed a negative effect on skin. This study explores the correlation between skin aging in the Asian population and levels of air pollutants to show different relationship between the two. This study was retrospective and included 389 patients, age between 30 and 74, who planned to receive a session of laser treatment for skin disorders in Kaohsiung Medical University Hospital (KMUH) from 2006 to 2019. Preoperative skin condition quantified by VISIA Complexion Analysis System (Canfield Imaging Systems, Fierfield, NJ, US). Eight air pollutants such as carbon monoxide (CO), non-methane hydrocarbon (NMHC), nitrogen oxides (NO, NO2, and NOx ), particulate matters (PM2.5 and PM10), ozone (O3 ), sulfur dioxide (SO2 ) and 8 skin condition such as spots, wrinkles, textures, pores, ultraviolet spots (UV spots), brown spots, red area, and porphyrin were analyzed to explore correlation between air pollution and skin aging. Strong correlation was found between NMHC exposure and texture, pores and brown spots formation. A positive correlation between O3 and better VISIA texture and pores scores was found. Brown spots was found to negatively associate with CO, NMHC, NO2, NOx, PM10, PM2.5, and SO2 . The skin condition of population over age 45 affected by CO, NMHC, NO2, NOx, PM2.5, PM10, and SO2 . Skin condition of the bottom 10% strongly correlates with exposure to PM10 and SO2, whereas skin condition of the top 10% was affected by PM10. Air pollutants such as CO, NO2, NOx, PM2.5, PM10, SO2, and NMHC were found to correlate with negative skin quality strongly. In contrast, O3 exposure is associated with less texture and pores. Future studies are warranted to further appreciate the relationships between air pollutants and skin condition.